THU0316 Gender differences in biologic treatment outcomes – a study of 1750 patients with psoriatic arthritis using danish health care registers. (12th June 2018) - Højgaard, P.; Ballegaard, C.; Cordtz, R.; Zobbe, K.; Clausen, M.; Kristensen, L.E.; Glintborg, B.; Dreyer, L.
Abstract : Background: Previous studies have shown conflicting findings on the impact of gender on effectiveness of tumour necrosis factor alpha inhibitor (TNFI) treatment in patients with psoriatic arthritis (PsA). Objectives: To investigate gender differences in disease manifestations, patient-reported outcomes, comorbidities and treatment effectiveness among patients with PsA treated with their first TNFI Methods: In this observational cohort study, the nationwide DANBIO register provided prospectively collected data on disease activity and treatment outcomes for PsA patients who initiated their first TNFI in 2000–2015. Data on comorbidities, diagnosed in hospital departments, were obtained by cross-linkage to the Danish National Patient Register. Treatment response was evaluated according to EULAR and ACR criteria at 3- and 6 months. Cox- and logistic regression models analysed the impact of gender on TNFI persistence and response, respectively, while adjusting for a priori selected confounders including clinical-, laboratory- and patient-reported factors, comorbidities and lifestyle characteristics Results: A total of 1750 PsA patients (53% females) were included. At baseline, women were older (49 years/47 years), more often smokers (32%/26%), had worse patient-reported scores (e.g. global score 71 mm/65 mm) and higher frequencies of hospital-diagnosed anxiety or depression (7%/4%) and chronic pulmonary disease (7%/3%), than men (all p<0.01). Median TNFI persistence was 3.8 years (95% CI 3.0–5.7) in men versus 1.4 (1.1–1.8) in women (p<0.001), figure 1. Men had higher odds of achieving response according to all response criteria, e.g. adjusted odds ratio=3.2 (1.6–6.1) for EULAR good/moderate response at 6 months (vs. women). Conclusions: Male patients had better TNFI treatment outcomes. Adjustment for baseline risk factors including patient-reported outcomes, disease activity, comorbidities and lifestyle factors did not influence this relationship, which suggests a role of biological factors. Acknowledgements: Thanks to patient-research partner Åse Stampe, to all patients and clinicians reporting to DANBIO, and to statistician Peder Frederiksen and biostatistician Robin Christensen for methodological and statistical advices. Thanks to the Oak Foundation, Danish Rheumatism Association, and Department of Rheumatology at Rigshospitalet, Gentofte. Disclosure of Interest: P. Højgaard Speakers bureau: Celgene and UCB, C. Ballegaard Speakers bureau: Janssen Pharmaceuticals, R. Cordtz: None declared, K. Zobbe: None declared, M. Clausen: None declared, L. Kristensen: None declared, B. Glintborg Grant/research support from: Abbvie, Biogen, Pfizer, L. Dreyer Speakers bureau: UCB and MSD